Short-term functional versus patient-reported outcome of the bicruciate stabilized total knee arthroplasty: prospective consecutive case series - Christen, Matthias (BMC Musculoskelet Disord, 2014)
BACKGROUND: The main goals of the standard treatment for advanced symptomatic knee osteoarthritis, total knee arthroplasty (TKA), are pain reduction and restoration of knee motion. The aim of this study was to analyse the outcome of the patient-based Knee Injury and Osteoarthritis Outcome Score (KOOS), and the surgeon-based Knee Society Score (KSS) and its Knee Score (KS) and Knee Functional Score (KFS) components after (TKA) using the Journey knee prosthesis, and to assess the correlation of these scores with range of motion (ROM). METHODS: In a prospective case series study between August 1(st) 2008 and May 31(st) 2011, 99 patients, all operated by a single surgeon, received Journey bicruciate stabilized total knee prostheses. The female/male ratio was 53/34, the mean patient age at surgery was 68 years (range 41–83 years), and the left/right knee ratio was 55/44. The KOOS, range of motion, and KS and KFS were obtained preoperatively and at 1-year follow-up. The pre- and postoperative levels of the outcome measures were compared using the Wilcoxon signed-rank test. Correlation between ROM and patient outcomes was analysed with the Spearman coefficient. RESULTS: All KOOS subscores improved significantly. Ninety percent of patients improved by at least the minimum clinically relevant difference of 10 points in stiffness and other symptoms, 94.5% in pain, 94.5% in activities of daily living, 84.9% in sports and recreation, and 90% in knee-related quality of life. The mean passive and active ROM improved from 122.4° (range 90-145°) and 120.4° (range 80-145°) preoperatively to 129.4° (range 90-145°) and 127.1° (range 100-145°) postoperatively. The highest correlation coefficients for ROM and KOOS were observed for the activity and pain subscores. Very low or no correlation was seen for the sport subscore. There was a significant and clinically relevant improvement of KSS (preop/postop 112.2/174.5 points), and its KS (preop/postop 45.6/86.8 points) and KFS (preop/postop 66.6/87.8 points) components. CONCLUSIONS: The Journey bicruciate stabilized knee prosthesis showed good 1-year postoperative results in terms of both functional and patient-based outcome. However, higher knee ROM correlates only moderately with patient-based outcome, implying that functionality afforded by the Journey bicruciate TKA is not equivalent to patient satisfaction. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/1471-2474-15-435) contains supplementary material, which is available to authorized users.